2017
DOI: 10.1128/aem.00628-17
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation Potential of Heat-Resistant Escherichia coli Dairy Isolates and the Complete Genome of Multidrug-Resistant, Heat-Resistant Strain FAM21845

Abstract: We tested the biofilm formation potential of 30 heat-resistant and 6 heat-sensitive Escherichia coli dairy isolates. Production of curli and cellulose, static biofilm formation on polystyrene (PS) and stainless steel surfaces, biofilm formation under dynamic conditions (Bioflux), and initial adhesion rates (IAR) were evaluated. Biofilm formation varied greatly between strains, media, and assays. Our results highlight the importance of the experimental setup in determining biofilm formation under conditions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 91 publications
(151 reference statements)
0
12
0
1
Order By: Relevance
“…Factors including incubation time, growth surface, and nutrients are thought to influence biofilm formation in staphylococci measured by static or dynamic model assays (Stepanović et al, 2001;Vanhommerig et al, 2014;Van Kerckhoven et al, 2016). Furthermore, we have recently shown similar results on biofilm formation of E. coli dairy isolates, noting a lack of correlation between static and dynamic conditions (Marti et al, 2017). From our results, we cannot conclude that differences observed in terms of biofilm formation are due only to the growth under flow conditions because the growth surface was not the same (polystyrene for the static model; glass in the dynamic model), which can influence the adhesion process.…”
Section: Discussionmentioning
confidence: 58%
“…Factors including incubation time, growth surface, and nutrients are thought to influence biofilm formation in staphylococci measured by static or dynamic model assays (Stepanović et al, 2001;Vanhommerig et al, 2014;Van Kerckhoven et al, 2016). Furthermore, we have recently shown similar results on biofilm formation of E. coli dairy isolates, noting a lack of correlation between static and dynamic conditions (Marti et al, 2017). From our results, we cannot conclude that differences observed in terms of biofilm formation are due only to the growth under flow conditions because the growth surface was not the same (polystyrene for the static model; glass in the dynamic model), which can influence the adhesion process.…”
Section: Discussionmentioning
confidence: 58%
“…Poor plant sanitation can allow for biofilm formation on these surfaces and become a source of contamination [ 9 ]. Many processing plants incorporate high temperatures into their cleaning procedures but limited research has been conducted thus far on whether heat resistance contributes to increased survival of E. coli in biofilms [ 43 ]. Furthermore, previous studies on the effect of environmental stressors on EHEC found it unlikely that strains could possess virulence genes for human infection and phenotypes for evading pathogen intervention measures in the food processing industry [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finalmente, también se ha identificado una interconexión entre las respuestas de adaptación al estrés y la formación de biopelículas, que podría ser la responsable de la mayor robustez de las células que conforman las biopelículas. Así, por ejemplo, el regulador de la respuesta general al estrés en bacterias Gram negativas, el factor alternativo RpoS, ha sido identificado como un factor clave para el establecimiento de biopelículas maduras en E. coli (Álvarez-Ordóñez et al, 2013;Chen et al, 2013) y también se ha observado un vínculo entre el potencial de formación de biopelículas de E. coli y su termorresistencia (Marti et al, 2017).…”
Section: Factores Que Determinan La Formación De Biopelículas En La Iunclassified